Detection of introduced microorganisms to rhizosphere - ZHANG Bing-xin; ZHANG Ping (浙江大学学报. 农业与生命科学版)
The microorganisms could be detected in rhizospere may be divided into two groups, the culturable and non-culturable. The culturable group could be detected by spontaneous antibiotic resistance; marker genes; DNA or RNA probe; and Immunofluorescent colony staining. But the first two methods are often combined to be used for culturable group. The second two methods are used to explore the colonization of culturable or non-culturable group including dead-cells and live-cells in rhizosphere. Lastly, the bigger progress in molecular microbial ecology in which non-culturable soil mioroorgamisms can be detected by genomic DNA libraries which can be used to explore soil microbial diversity including the colonzation of introduced microbes to rhizosphere.